Pengaruh Kualitas Pelayanan, Store Atmosphere, dan Variasi Menu terhadap Minat Beli Konsumen Coffee Shop Addicted Coffee & Eatery, Sukawati, Gianyar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
The reason of this ponder is to decide the impact of benefit quality, store environment, and menu varieties on buyer buying intrigued. The area of this inquire about was carried out within the city of Sukawati, Gianyar and the test utilized was 80 respondents utilizing the accidential strategy or (comfort testing). The information examination procedures utilized are legitimacy tests, riliability, classical suspicions, numerous direct relapse, coefficient of assurance, t test and F test. From the comes about of the think about, it can be seen that the quality of benefit incorporates a noteworthy positive impact on customer buying intrigued, store environment features a critical positive impact on customer buying intrigued, and menu varieties have a critical positive impact on buyer buying intrigued and benefit quality, store air, and menu varieties at the same time have a positive and critical impact on shopper buying intrigued. The size of the impact of the free variable on customer buying intrigued was 73.4 percent.